Seroprevalence and Risk Factors of Neospora caninum Infection among Dairy Cows in the Western Provinces of Nakhon Pathom, Ratchaburi and Kanchanaburi, Thailand - Arunvipas, Pipat; Inpankaew, Tawin; Jittapalapong, Sathaporn (Agriculture and Natural Resources, 2012)
A total of 300 dairy cow sera from 60 dairy herds from three provinces (Nakhon Pathom, Ratchaburi and Kanchanaburi) in western Thailand were collected and examined for antibodies against N. caninum infection by competitive enzyme-linked immunosorbent assay and an indirect fluorescent antibody technique. Of these, 10% were positive to N. caninum infection and the herd prevalence was 35% (21/60). The presence of domestic dogs on the farms did not demonstrate a signiﬁ cant association with N. caninum infection in this study. Multiple logistic regression was used to evaluate the association between the risk variables collected from questionnaires and sero-positivity to N. caninum infection among dairy cows. A herd with the presence of backyard chickens was 2.7 times more likely to be seropositive than those herds without chickens (P = 0.01) and herds with rats on the farms were 3.5 times more likely to get infected. Seropositive cows tended to have a higher risk of abortion than seronegative animals (odds ration = 2.4, P = 0.08) which suggested that N. caninum could potentially be a major cause of abortion among dairy cows in western Thailand.